Respostas

2014-02-04T12:33:05-02:00
(a+3) ^{2} \\ (a+3).(a+3)  \\  a^{2} +3a + 3a + 9 \\ \boxed{a^{2} + 6a + 9}


a² +6a+ 9 ~> a = 1 , b = 6 , c = 9

Δ = b² - 4ac
Δ = 6² - 4.1.9
Δ = 36 - 36
Δ = 0

a = -b ± 
√Δ
        2a

a = -6 ± √0
         2.1

a = -6 ± 0
         2

a' = -6 + 0  = -6  = -3                a" = -6 - 0  = -6 = -3
         2         2                                   2         2

S = {-3;-3}
1 5 1
2014-02-04T12:40:26-02:00
(a + 3) . (a +3)                                 x= -6 +/- 0
a² + 3a + 3a + 9                                    ---------
a² + 6a + 9 = 0                                          2
Δ= (6)² - 4.a.c
Δ= 36 - 4.1.9                                     x' = -6 + 0 = -3
Δ= 36 - 36                                               -------
Δ= 0                                                          2
x= - 6 (1) +/- √0                           x'' = -6 - 0 = -3
     -----------------                                   --------
          2.1                                              2

Resposta: -3 e -3.
1 5 1